Climate change and adaptation through the human security lens: insights from the Mekong Delta - Le, Phuong-Dung; Pacillo, Grazia; Läderach, Peter; Long, Hoang; Van Dijk, Han (Liverpool University Press, 2025)
Climate change poses significant threats to the livelihoods of farmers, particularly in coastal regions where drought, salinity intrusion and weather variability reduce crop yields and increase poverty. While climate adaptation strategies aim to mitigate these impacts, they do not necessarily translate into positive outcomes. Through a scoping literature review and in-depth interviews, the paper investigates different domains of human (in)security and their interactions in the context of significant climate change impacts and relatively rapid adaptive responses within the Vietnamese Mekong Delta. The analysis shows that not only several critical manifestations of insecurity arise due to climate change impacts, but also unexpected human insecurity and potential conflict risks can happen as the result of climate adaptation activities. We conclude that a holistic understanding and mainstreaming of human security into adaptation planning and implementation for the region is important and requires more attention from both research and policy perspectives. This article was published open access under a CC BY licence: https://creativecommons.org/licenses/by/4.0/ .